PENINGKATAN SOFTSKILL MAHASISWA PADA MATERI SISTEM SOSIAL MELALUI PEMBELAJARAN MEDIA MINDSCAPE DAN DISKUSI KOOPERATIF - Esti Sarjanti (Khazanah Pendidikan, 2010)
This research was aimed at improving students softskill on the topic of social system through cooperative discussion and mindscape learning. This action research was done in two cycles and meant to get data on lecturers and student activity as well as the softskill of 45 PGSD students of University Muhammadiyah Purwokerto. The data include their initiatives, integrity, self concept, creativity, critical-thinking ability, commitment, learning motivation. Data was taken through observation and analyzed descriptively to know their learning activities which where categorized from less active to active, while the softskill was categorized from lacking to good. The result showed that lecturers activity which were already good were able to improve the students softskill in the aspect of integrity/ cooperating ability, learning commitment and motivation. The other aspect of students softskill were still in medium level category and needed to be improved. Key words: softskill, cooperative, dan mindscape